Bahasa Inggris - Rahman, Nurain; Agusrianto Yusuf; Mindy Eka Astuti (Journal of Health, Technology and Science (JHTS), 2023)
Escherichia coli is a normal bacterial flora that is often found in the human intestine, is unique because it can cause primary infections such as diarrhea.This study aims to identify or see the presence or absence of Escherichia coli bacteria in fruit ice sold by street vendors in Gorontalo City.Methods in researchit uses a qualitative approach. The type of research used is descriptive observational where research on the presence of Escherichia coli bacteria is carried out on fruit ice drinks according to the results of laboratory tests carried out. The sampling technique used is random sampling and there are 8 locations of fruit ice sellers in Gorontalo City.Research result What has been done is that all samples that have been examined are not contaminated with Escherichia Coli bacteria but are contaminated or contaminated by other pathogenic bacteria.